Hubungan Kualitas Mikrobiologis Air Sumur Gali dan Pengelolaan Sampah di Rumah Tangga dengan Kejadian Diare pada Keluarga di Kelurahan Terjun Kecamatan Medan Marelan Tahun 2013 - marina aprina; Evi Naria; Wirsal Hasan (Lingkungan dan Kesehatan Kerja, 2014)
Correlation the quality of microbiological dug well water and management of domestic waste with the incidence of diarrhea at family in Terjun Village District Marelan 2013. The source of clean water which is mostly used by society is dug well. Dug well is easily contaminated by bacterial from the source of pollution. It can cause the disease like diarrhea. Moreover, waste is the source of disease too and the breeding ground of vector like fly.The purpose of this research was to know correlation between the quality of microbiological water of dug well and description management of domestic waste with the incidence of diarrhea at family in Terjun Village District Marelan.This research used the cross sectional design, to know how the correlation the quality of microbiological water of dug well with the incidence of diarrhea and description management of domestic waste. This population are family in environment 20. And do the examination of dug well water in respondent’s house with taking sampel by purposive sampling.The Result showed that the quality of microbiological water of dug well are the Total of uneligible coliform is 73,30% of water samples and the uneligible Escherichia coli is 90% of water samples. All family (100%) do not seperation the waste, all family do not provide the eligible trash, method of waste destruction that good is 83,30% and not good is 16,70%. Diarrhea happened in every member family is 33,30%. There is no corellation between the quality of the microbiological water with the incidence of diarrhea (p=1,000) and (p=0,251). Puskesmas should be made the socialization to use the water filter and the water sanitation. The society provide the eligible trash, do separation the waste, and keep healthy behavior of use the water. Keywords: the quality of microbiological water, management of waste, diarrhea